Literature Review Mengukur Kinerja Karyawan Pada Bidang Jasa Dan Manufaktur - Nurjannah, Nurjannah; Tyas, Ari Anggarani Winadi Prasetyoning; Cahyadi, Lukman (Universitas Muhammadiyah Tangerang, 2024)
In the world of work, both in industry and in institutions, human resources (HRM) are a very important component. A strong and reliable human resource is essential to the smooth operation of any company. It's an essential part of any organization's ability to compete in today's market, and every company is trying to find the best individual to do it. If a company wants to its vision, mission, and goal, human resource management needs to be given greater attention. So, whatever affects employee performance should be taken into account. This research analyzes the things that influence the performance of employees in the company, because of the importance of human resources for the competitive advantage of the company. The purpose of this writing is to find out how advanced research is related to the topic. The method used in this research is literature review. Research results show that employee performance is strongly influenced by job motivation. Therefore, human resource management is vital to having good employees and performing optimally.